Perancangan Aplikasi Monitoring Stok Berbasis Web dengan Optimalisasi Tingkat Persediaan pada PT Nandya Karya Perkasa - Rizal, Muhammad Alde; Ramadhan, Muhamad Rivan Ardiansyah; Hardiman, Hendi Dwi; Diningrat, Mohammad Santosa Mulyo; Saidatuningtyas, Ifa (Institut Teknologi Adhi Tama Surabaya, 2025)
PT Nandya Karya Perkasa is a manufacturing company that produces motor vehicle spare parts. PT Nandya Karya Perkasa supplies its products to several automotive companies. The company faces issues with its inventory due to frequently fluctuating demand, often leading to order cancellations. Data from the past three months shows the company had to cancel approximately 19% of orders. This issue arises because of the limitations of the previously used application. Some crucial data, such as stock levels, which should support decision-making, is still missing, as the existing system only focuses on recording goods' inflows and outflows. This study aims to propose improvements to the use of the Inventory Management System application to facilitate the planning department in planning the production process, ensuring the availability of goods in the warehouse to meet all consumer demands. The method used to address this problem is a web-based application for monitoring goods, which can provide feedback for production planning improvements in case of demand changes. The system is developed using the Prototype method. A two-month trial has shown a reduction in order cancellations to 11%.